O esperançar da cidade educadora - Jaqueline Andrade; Alina Gonçalves Santiago (Cidades, Comunidades e Território)
Our understanding of the socio-educative process goes beyond the school and the family, including non-formal and informal dimensions. The interaction between these dimensions creates a complex net of education, where the city is the main scenario of pedagogical practices. The urban space provides a diversity of educational opportunities, fostering the development of citizens through social interaction, awareness of territory and reinforcement of belonging and collective identity. This research aims to analyze how the city acts as educating agent in citizen formation. Using a multi-method approach, we seek to comprehend the relation between educational dimensions by exploring the potentialities and limitations of Monte Serrat and Campeche communities, in Florianópolis. The case studies reveal the learning opportunities, highlighting the impact of the city in education. However, some challenges have been identified, as the lack of proper urban spaces for kids and teenagers, socio-spatial segregation and the need for broader community participation. The constitution of inclusive environments and the development of formal, non-formal and informal education emerge as essential for an effective educating city. Summarily, this research sheds light on the value of the city as an educational agent, emphasizing the need to overcome challenges to promote a whole and inclusive education. The achievements reinforce the importance of actions that encourage participation of all community members, towards the construction of genuine educating cities.